South Toewr, Court of the Moon, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
The south Towers of the Fair's center group, present a brilliant spectacle by night. Soft hidden lights, in ground trenches, behind shrubs, and in building recesses, give the Palaces, unusual and striking appearances, a symphony of blue, amber, orchid, flame and jade coloring.